SOCIAL CLIMBING SEBAGAI AKTUALISASI DIRI KAUM MARJINAL (STUDI DESKRIPTIF DI KALANGAN REMAJA JAKARTA SELATAN) - Jaduk Gilang Pembayun (Universitas Tidar, 2018)
This research was conducted to examine and analyze the ways of communicating in a